A Perspective on Polo-Like Kinase-1 Inhibition for the Treatment of Rhabdomyosarcomas - Gatz, Susanne A.; Aladowicz, Ewa; Casanova, Michela; Chisholm, Julia C.; Kearns, Pamela R.; Fulda, Simone; Geoerger, Birgit; Schäfer, Beat W.; Shipley, Janet M. (Frontiers in Oncology, 2019)
Rhabdomyosarcomas are the most common paediatric soft tissue sarcoma and are a major cause of death from cancer in young patients requiring new treatment options to improve outcomes. High-risk patients include those with metastatic or relapsed disease and tumours with PAX3-FOXO1 fusion genes that encode a potent transcription factor that drives tumourigenesis through transcriptional reprogramming. Polo-Like Kinase-1 (PLK1) is a serine/threonine kinase that phosphorylates a wide range of target substrates and alters their activity. PLK1 functions as a pleiotropic master regulator of mitosis and regulates DNA replication after stress. Taken together with high levels of expression that correlate with poor outcomes in many cancers, including rhabdomyosarcomas, it is an attractive therapeutic target. This is supported in rhabdomyosarcoma models by characterisation of molecular and phenotypic effects of reducing and inhibiting PLK1, including changes to the PAX3-FOXO1 fusion protein. However, as tumour re-growth has been observed, combination strategies are required. Here we review preclinical evidence and consider biological rationale for PLK1 inhibition in combination with drugs that promote apoptosis, interfere with activity of PAX3-FOXO1 and are synergistic with microtubule-destabilising drugs such as vincristine. The preclinical effects of low doses of the PLK1 inhibitor volasertib in combination with vincristine, which is widely used in rhabdomyosarcoma treatment, show particular promise in light of recent clinical data in the paediatric setting that support achievable volasertib doses predicted to be effective. Further development of novel therapeutic strategies including PLK1 inhibition may ultimately benefit young patients with rhabdomyosarcoma and other cancers.